Prevention and Handling of Maladministration in Population Administration Services:A Case Study at the Semarang City Civil Registration Office - Aqila Acyuta Endrosava; Ratih Damayanti (Annual Review of Legal Studies, 2026)
Population administration services constitute an essential part of public services as they are directly related to the fulfillment of citizens’ administrative rights and legal certainty. However, in practice, the provision of such services is often still confronted with maladministration issues. This study aims to analyze the forms of maladministration, their conformity with the principles of public service, as well as the efforts to prevent and address maladministration in population administration services at the Population and Civil Registration Office (Disdukcapil) of Semarang City. This research employs an empirical legal method (socio-legal approach) with a descriptive qualitative approach. Data were collected through in-depth interviews with Disdukcapil officials, operators of the Digital Population Identity (IKD) application, internship students, and service users, supported by observation and documentation studies. The results indicate that maladministration persists in the form of an inefficient queue system at certain times, the implementation of the IKD application that is not yet inclusive for vulnerable groups such as the elderly, and the placement of human resources lacking adequate competence in strategic service positions. These findings demonstrate that the principles of legal certainty, effectiveness, non-discrimination, professionalism, and accountability as stipulated in Law Number 25 of 2009 on Public Services have not been optimally implemented. This study concludes that improving the quality of population administration services requires not only digital innovation but also the strengthening of human resources, inclusive service delivery, and effective oversight mechanisms to prevent and address maladministration.